Enhancing the Reading Development of Learners with Autism Spectrum Disorder - Whalon, Kelly (Seminars in Speech and Language, 2018)
Foundational to autism spectrum disorder (ASD) are difficulties developing joint attention, social reciprocity, and language/communication. These challenges place children with ASD at risk for future reading failure. Research suggests that many school-aged children with ASD will learn the decoding skills necessary to effectively read text, but will struggle with comprehension. Yet, the reading profiles of learners with ASD also show great heterogeneity, with some also unable to effectively decode new words. The range of challenges associated with ASD highlights the need for comprehensive literacy/reading instruction that addresses both code- and meaning-focused skills from the earliest grades. This article will provide an overview of effective interventions that support both the code- and meaning-focused skills of learners with ASD. Specific examples of effective instructional practices for learners with ASD will be shared.
Keywords: Autism; reading; comprehension; phonics; intervention